2009
DOI: 10.1002/clc.20616
|View full text |Cite
|
Sign up to set email alerts
|

Oral L‐arginine Supplementation in Acute Myocardial Infarction Therapy: A Meta‐analysis of Randomized Controlled Trials

Abstract: Objective:The objective was to analyze completed trials assessing the effect of oral L-arginine supplementation on clinical outcomes of patients with acute myocardial infarction (AMI). Background: Prior trials suggest that oral L-arginine administration improves endothelial function in patients with stable coronary artery disease (CAD). However, it is still unclear whether oral supplementation of L-arginine has any effect on clinical outcomes in patients with unstable CAD, such as AMI. Methods: We systematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…On the other hand, another randomized controlled trial in post-MI patients, again using 9 g of arginine daily, but of only 1-month duration, found a non-significant trend toward protection with arginine (Bednarz et al 2005). A meta-analysis which incorporated these two trials found no impact of arginine on mortality risk (RR = 0.93; 95 % CI 0.74-1.17) (Sun et al 2009).…”
Section: A Note On Argininementioning
confidence: 98%
“…On the other hand, another randomized controlled trial in post-MI patients, again using 9 g of arginine daily, but of only 1-month duration, found a non-significant trend toward protection with arginine (Bednarz et al 2005). A meta-analysis which incorporated these two trials found no impact of arginine on mortality risk (RR = 0.93; 95 % CI 0.74-1.17) (Sun et al 2009).…”
Section: A Note On Argininementioning
confidence: 98%
“…Imipramine improves angina, possibly through visceral analgesic, anticholinergic, and alpha-antagonist effects (104). L-arginine improved angina and vascular function (105), but was adverse in an obstructive CAD trial (106). Postmenopausal hormone therapy improved emotional well-being, but had no effect on angina or exercise tolerance (107).…”
Section: Clinical Trials To Provide Evidence-based Guideline Developmentmentioning
confidence: 99%
“…Such investigations have primarily studied interventions that can enhance vascular NO levels for the treatment of endothelial dysfunction and include enhancing L-arginine substrate bioavailability 58,59 and introducing antioxidants to limit the destruction of NO by reactive oxidant species 60,61 . Unfortunately, studies investigating the chronic administration of these agents suggests that such interventions lack clear efficacy and in some cases worsen outcome, although it should be noted that there are inherent complexities with the design of these types of clinical trial [62][63][64][65][66] .…”
Section: Regulation Of Nitric Oxide Bioavailabilitymentioning
confidence: 99%